Adaptive Strategies in HR Performance Management in Multinational Companies: Integration, Modernization, and Knowledge Sharing - Dr. Abdul Wahab Samad (PT. Mega Mas Abadi Konsultan, 2025)
Human resource performance management in multinational enterprises (MNEs) faces complex challenges due to cultural differences, organizational structures, and global dynamics. This article examines the Integrated Performance Management (IPM) system in an international context, highlighting the importance of knowledge sharing and modernization of management structures. Through a qualitative approach, this study explores strategies for designing and implementing an effective performance system to support MNEs' strategic goals. The key findings indicate that flexibility and local adaptation are crucial factors in ensuring the success of a global performance management system while maintaining alignment with the organization's vision. The study's implications suggest that MNEs must develop more dynamic, data-driven, and context-responsive performance management policies. Furthermore, the synergy between digital technology and knowledge-sharing practices can accelerate system adaptation, enhance employee engagement, and strengthen corporate competitiveness on a global scale.